2001
DOI: 10.1034/j.1600-0455.2001.420608.x
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of inner ear dysplasias in patients with sensorineural hearing loss . High-resolution MR imaging and volume-rendered reconstructions

Abstract: The imaging protocol allows for rapid and comprehensive visualization of various IE dysplasias, based on a limited number of VR reconstructions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…It is clear that both magnetic resonance imaging (MRI) and computed tomography (CT) are able to sufficiently define the architecture of the otic capsule. While CT is superior for assessing intratemporal facial nerve location, inner ear ossification, and temporal bone pathology, recent studies have demonstrated that MRI provides superior definition of the soft tissues of the auditory system proximal to the inner ear including the cochlear nerve and brain (15,19,21,22,24). Moreover, MRI can better assess post-meningitic fibrosis of the labyrinth that has not yet undergone ossification (21).…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that both magnetic resonance imaging (MRI) and computed tomography (CT) are able to sufficiently define the architecture of the otic capsule. While CT is superior for assessing intratemporal facial nerve location, inner ear ossification, and temporal bone pathology, recent studies have demonstrated that MRI provides superior definition of the soft tissues of the auditory system proximal to the inner ear including the cochlear nerve and brain (15,19,21,22,24). Moreover, MRI can better assess post-meningitic fibrosis of the labyrinth that has not yet undergone ossification (21).…”
Section: Introductionmentioning
confidence: 99%
“…5,[7][8][9] Both plain film and CT, however, define mainly the bones that contain the actual working components of inner ear hearing. Previous studies, 9,10 however, have shown that high-resolution magnetic resonance imaging (MRI) used as a diagnostic tool in the evaluation of pediatric SNHL has yielded promise in better defining the exact soft tissue abnormalities of the hearing pathway rather than their bony housing. Specifically, MRI provides better ability to directly visualize the cochlear nerve and intracranial structures.…”
mentioning
confidence: 99%
“…Radiologic studies and magnetic resonance imaging of the mastoid and middle ear showed several types of middle and inner ear pathology, among them: (1) hypoplasia, malformation and displacement of the ossicular chain, such as the junction of the hammer and anvil fixing the malleus in the tympanic membrane, and calcified oval window; (2) malformations—enlargement—and asymmetry of the semicircular canals/ducts and endolymphatic sac; and (3) cochlear hypoplasia or dysplasia. 6 7 14 49 50 53 56 57 58 …”
Section: Resultsmentioning
confidence: 99%